2018
DOI: 10.1002/pssa.201800578
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Evolution of Mechanically Deformed Polycrystalline Silicon for Kerfless Photovoltaics

Abstract: Silicon wafers for photovoltaics could be produced without kerf loss by rolling, provided sufficient control of defects such as dislocations can be achieved. A study using mainly high resolution electron backscatter diffraction (HR‐EBSD) of the microstructural evolution of Siemens polycrystalline silicon feedstock during a series of processes designed to mimic high temperature rolling is reported here. The starting material is heavily textured and annealing at 1400 °C results in 90% recrystallization and a red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Advancements in processing and cell technologies since the mid-2000s have paved the way for high-efficiency thin silicon devices to enter the market; [1] therefore, a revisiting of module reliability based on kerfless wafers is warranted. Detailed reviews of kerfless wafering technologies can be found in other studies, [1][2][3][4][5][6][7][8] and examples include implant and cleave, [4,9] exfoliation and spalling, [10][11][12][13][14][15] blade cut, [16] laser processes, [17] dendritic web growth, [18,19] string ribbon growth, [20][21][22] direct wafering, [23] the floating silicon method, [24,25] and epitaxial growth. [1,26,27] Epitaxial growth, for example, has shown 4.5 ms carrier lifetime and high (> 20%) efficiencies [26] and shows 4.6-7.0 ms carrier lifetime after phosphorus gettering (before, 1.9-4.3 ms), [27] though there is opportunity for further improvements.…”
Section: Introductionmentioning
confidence: 99%
“…Advancements in processing and cell technologies since the mid-2000s have paved the way for high-efficiency thin silicon devices to enter the market; [1] therefore, a revisiting of module reliability based on kerfless wafers is warranted. Detailed reviews of kerfless wafering technologies can be found in other studies, [1][2][3][4][5][6][7][8] and examples include implant and cleave, [4,9] exfoliation and spalling, [10][11][12][13][14][15] blade cut, [16] laser processes, [17] dendritic web growth, [18,19] string ribbon growth, [20][21][22] direct wafering, [23] the floating silicon method, [24,25] and epitaxial growth. [1,26,27] Epitaxial growth, for example, has shown 4.5 ms carrier lifetime and high (> 20%) efficiencies [26] and shows 4.6-7.0 ms carrier lifetime after phosphorus gettering (before, 1.9-4.3 ms), [27] though there is opportunity for further improvements.…”
Section: Introductionmentioning
confidence: 99%
“…An important process step in this route is the directional solidification of the MG-Si [1][2][3][4][5] to induce segregation of metallic impurities to the silicon ingot top. Although mechanical properties of silicon play a secondary role in the efficiency of photovoltaic cells [6], its lack of ductility [7] and toughness [8] affects the production of silicon wafers and solar panels and makes the mechanical conformation of silicon practically impossible. Toughness measurements of SoG-Si produced by directional solidification of MG-Si are not easily found in the literature.…”
Section: Introductionmentioning
confidence: 99%